Hubungan Antara Konsep Diri Peserta Didik Dengan Hasil Belajar Pada Mata Pelajaran Ekonomi Di Kesetaraan Paket C SPNF SKB - Revi Yuni Azhari; Setiawati Setiawati (Universitas Negeri Padang, 2022)
The research is the low learning outcomes of students in economics at SPNF SKB Solok City. This condition is believed to be due to the low self-concept of students. This study has the objectives to: 1) see a description of the students' self-concept in the economic learning package C program at SPNF SKB Solok City, 2) see a description of their learning outcomes in the economic learning package C program at SPNF SKB Solok City 3) see the relationship between self-concept students with their learning outcomes in economic subjects Package C Equivalence Program at SPNF SKB Solok City. This research was conducted with a quantitative approach of correlation type which aims to examine the relationship between self-concept and learning outcomes. The research population is all students registered in Package C 2021 at SPNF SKB Solok City as many as 31 people, the sampling technique is stratified random sampling and taken as many as 80%, namely as many as 25 people. The data collection method used a questionnaire with a statement list format as a data collection tool, the data were analyzed using the percentage formula and to find the correlation using the Spearmen Rho formula. The results of the study prove that 1) the description of the self-concept of students in the economic subject of the Package C Equivalence Program at SPNF SKB Solok City which is still relatively low 2) the learning outcomes of students in economic learning are low, and 3) there is a significant relationship between self-concept of students with student learning outcomes in economic subjects Package C Equivalence Program at SPNF SKB Solok City. It is hoped that tutors can develop a positive self-concept for students who take part in the economics subject of the Package C Equivalence Program, the next researcher to examine other variables that can improve the learning outcomes of equivalence education